Microperla qinlinga Chen reviewed with supplementary illustrations and the description of the nymph - Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2019)
Microperla qinlinga Chen, 2019 was recently described, but details of the aedeagus were not included in the original description. In this paper, the male aedeagus and nymph of M. qinlinga are described for the first time. Additional information concerning the genus Microperla Chu, 1928 is discussed.